Associations Between AUDIT-C and Mortality Vary by Age and Sex - Harris, Alex H.S. (Mary Ann Liebert, Inc., 2010)
We sought to determine the sex- and age-specific risk of mortality associated with scores on the 3-item Alcohol Use Disorder Identification Test–Consumption (AUDIT-C) questionnaire using data from a national sample of Veterans Health Administration (VHA) patients. Men (N = 215,924) and women (N = 9168) who completed the AUDIT-C in a patient survey were followed for 24 months. AUDIT-C categories (0, 1–4, 5–8, 9–12) were evaluated as predictors of mortality in logistic regression models, adjusted for age, race, education, marital status, smoking, depression, and comorbidities. For women, AUDIT-C scores of 9–12 were associated with a significantly increased risk of death compared to the AUDIT-C 1-4 group (odds ratio [OR] 7.09; 95% confidence interval [CI] = 2.67, 18.82). For men overall, AUDIT-C scores of 5–8 and 9–12 were associated with increased risk of death compared to the AUDIT-C 1-4 group (OR 1.13, 95% CI = 1.05, 1.21, and OR 1.63, 95% CI = 1.45, 1.84, respectively) but these associations varied by age. These results provide sex- and age-tailored risk information that clinicians can use in evidence-based conversations with patients about the health-related risks of their alcohol consumption. This study adds to the growing literature establishing the AUDIT-C as a scaled marker of alcohol-related risk or “vital sign” that might facilitate the detection and management of alcohol-related risks and problems. (Population Health Management 2010;13:263–268)